The future of peace psychology in Asia - Noor, Noraini M. (Springer, 2009)
The theories and practices of peace psychology in Asia are conditioned by a host of cultural, historical, and social-political factors in this part of the world. Christie, Wagner, and Winter (2001), Christie (2006), and Christie, Tint, Wagner, and Winter (2008) claim that violence and peace are expressions of the interactions among these macro factors. Montiel, in the introductory chapter of this volume, likewise stresses the embeddedness of social violence and peace in multiple macro-layers and the interconnectedness of social violence and peace. She succinctly argues that due to Asia’s rich history of peace and conflict, peace psychology in the region will likewise negotiate its course in reference to the legacies of its political history. Christie (2006) emphasizes the 2 × 2 systems perspective that violence and peace are expressed in both direct and structural forms.